Hedging Effectiveness of Asean-3 Stock Index Futures; A Comparative Analysis of Static and Dynamic Models On in and Out-Sample Periods - Uliwa, Catherine Peniel (2016)
Adverse impact of recent varying uncertainties on stock index portfolios has stimulated investors’ need to use risk management tools to hedge their investments. However, studies giving investors and other stakeholders awareness on the effectiveness of stock index risk management tools like stock index futures in emerging markets is minimal. Furthermore the ongoing controversy on the performance of constant and dynamic hedge ratio estimation techniques leave investors unaware of an appropriate technique to adopt in these markets to attain an effective hedge. This paper investigates the hedging effectiveness of selected ASEAN-3 (Singapore, Thailand and Malaysia) stock index futures through a comparative analysis of three constant (OLS, VAR, VECM) and two dynamic (MVGARCH, MVGARCH-ECM) hedge ratio estimation models. Using an estimation period from 1st January 2007 to 31st November 2014 involving various volatility shifts; the paper estimates the hedge ratio within the period and evaluates effectiveness within the period as well as forecasting effectiveness on short in and out-sample periods. Hedging effectiveness is evaluated based on risk minimization and utility maximization. Although the in sample results are slightly mixed in terms of model superiority in risk minimization and utility maximization; the results conclude that the MVGARCH-ECM dynamic model that accounts for time varying nature of spot and futures as well as short run disequilibrium is most effective in risk minimization as well as utility maximization on the most reliable out-sample forecast. MVGARCH-ECM proves to be a good out-sample hedge ratio forecasting methodology. Singapore’s STI Futures are observed to have the highest effectiveness in reducing risk across the estimation period that includes extreme volatility and calmness, as well as the in and out sample short forecasting periods; followed by Thailand’s SET-50 Index Futures and finally the FTSE Kuala Lumpur Composite Index futures.